1998
DOI: 10.1002/(sici)1097-0096(199806)26:5<247::aid-jcu3>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Doppler flow characteristics in patients with pelvic inflammatory disease: Responders versus nonresponders to therapy

Abstract: Purpose The objective of this retrospective study was to evaluate the role of Doppler flow studies in predicting the response to antibiotic treatment in patients with pelvic inflammatory disease (PID). Methods The resistance indices in pelvic masses of 24 patients with clinical diagnoses of PID were analyzed. Results Twelve patients responded favorably to antibiotic treatment (the conservative treatment group), while the other patients showed no clinical improvement and underwent surgery (surgical treatment gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 5 publications
(5 reference statements)
5
8
0
1
Order By: Relevance
“…Pelvic USG has proven to be a useful complementary tool in the diagnosis of PID in adolescents. 21,22 In our study, USG compatible with PID was present in 40% of adolescents with an STI. This high rate could be associated with the sonographers' awareness of the suspected diagnosis.…”
Section: Discussionsupporting
confidence: 55%
“…Pelvic USG has proven to be a useful complementary tool in the diagnosis of PID in adolescents. 21,22 In our study, USG compatible with PID was present in 40% of adolescents with an STI. This high rate could be associated with the sonographers' awareness of the suspected diagnosis.…”
Section: Discussionsupporting
confidence: 55%
“…Vascular resistance increased as the infection subsided. Tepper et al 22 found that Fallopian tube arterial resistance decreased with increasing severity of PID. Thus, these studies consistently show that acute inflammation causes hyperemia, leading to a decrease in vascular resistance seen with color Doppler, and that increasing vascular resistance reflects recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Even though acutely inflamed tubes are richly vascularized at color Doppler [16,15,17,6,5], our review shows that spectral Doppler results overlap too much between women with and without acute PID for them to be useful in isolation in the diagnosis of acute PID [6,5]. Color/power Doppler findings on the other hand might be useful for discriminating between acute and chronic PID, acutely inflamed tubes being more richly vascularized at power Doppler than chronic hydrosalpinges [19].…”
Section: Discussion/summary Of Evidencementioning
confidence: 90%
“…In women with a clinical diagnosis of acute PID, changes in blood flow velocities in the pelvic vessels before, during and after antibiotic treatment have been observed by performing serial spectral Doppler ultrasound examinations. In the acute phase of the infection, the vascular resistance (pulsatility index, resistance index) in the uterine arteries [15,16], tubo-uterine and ovarian arteries [16] and arteries of pelvic masses [17] was low but returned to normal when the infection subsided [16,15,17].…”
Section: Doppler Velocimetrymentioning
confidence: 99%